News media representation of China’s three-child policy in China daily: a corpus-assisted critical discourse analysis - Can, Wang; Mohammad Fadzeli Jaafar,; Anis Nadiah Che Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Since 2021, China has implemented the three-child policy to address the demographic problems arising from an ageing population and a low birthrate. The representation of the policy in newspapers holds an important position in its communication and interpretation. However, critical discourse analysis of the newspaper coverage on this policy remains scarce, especially when approached through a corpus-assisted methodology. Therefore, this study conducts a corpus-assisted critical discourse analysis of the representation of China’s three-child policy. Four hundred twentyone news articles were collected from China Daily, and keyword analysis and concordance analysis were conducted to identify the topics of the news articles and the argumentation strategies adopted. The findings reveal three main topics within the news articles, namely social and economic matters, national/regional entity and social identity, along with a variety of topoi used to legitimise the stated claims. This study provides insights into how the three-child policy is represented in China’s English-language newspaper.